Janus Kinase Inhibition in the Aicardi–Goutières Syndrome - Vanderver, Adeline; Adang, Laura; Gavazzi, Francesco; McDonald, Katherine; Helman, Guy; Frank, David B; Jaffe, Nicole; Yum, Sabrina W; Collins, Abigail; Keller, Stephanie R; Lebon, Pierre; Meritet, Jean-François; et al. (The New England journal of medicine, 2020)
Patients with the Aicardi–Goutières syndrome, an autosomal recessive disorder that affects the central nervous system, immune system, and skin, have severe neurodevelopmental abnormalities and abnormal signaling in the interferon pathway. In patients in this study, Janus kinase inhibition decreased skin manifestations and improved neurologic function.